Benefits and Challenges in the Incorporation of Insects in Food Products - Acosta-Estrada, Beatriz A.; Reyes, Alicia; Rosell, Cristina M.; Rodrigo, Dolores; Ibarra-Herrera, Celeste C. (Frontiers in Nutrition, 2021)
Edible insects are being accepted by a growing number of consumers in recent years not only as snack but also as side dish or ingredient to produce other foods. Most of edible insects belong to one of these groups of insects such as caterpillars, butterflies, moths, wasps, beetles, crickets, grasshoppers, bees and ants. Insect properties are analyzed and reported in the articles reviewed here and one common feature is nutrimental content, which is one of the most important characteristics mentioned, especially proteins, lipids, fiber, and minerals. On the other hand, insects can be used as substitute of cereals’ flour for the enrichment of snacks because of their high content of proteins, lipids and fiber. Technological properties are not altered when these insects-derived ingredients are added and sensorial analysis is satisfactory, and only in some cases change in color takes place. Insects can be used as substitute ingredients in meat products; the products obtained have higher mineral content than traditional ones and some texture properties (like elasticity) can be improved. In extruded products, insects are an alternative source of proteins to feed livestock showing desirable characteristics. Isolates of insect’s proteins have demonstrated bioactive activity, and these can be used to improve food formulations. Bioactive compounds, as antioxidant agents, insulin regulators and anti-inflammatory peptides, are high-value products that can be obtained from insects. Fatty acids play a significant role in human health and lipids from insects have showed positive impacts in coronary disease, inflammation and cancer. Insects can be a vector for foodborne microbial contamination, but the application of good manufacturing practices, effective preservation techniques jointly with the development of appropriate safety regulations will decrease the appearance of such risks. However, allergens presented in some insects are a hazard that must be analyzed and taken into account. Despite all the favorable health-promoting characteristics present in insects and insects-derived ingredients, willingness to consume them has yet to be generalized.